ANALISIS YURIDIS RESIKO PEMALSUAN TERHADAP PENGADAAN SERTIFIKAT ELEKTRONIK DI INDONESIA - Muhammad Chafi Sholeh (Fakultas Hukum Universitas Islam Malang, 2021)
ABSTRACThe issuance of Ministerial Regulation of ATR BPN Number 1 of 2021 concerning Electronic Certificates is a progressive regulation with the intention of replacing conventional certificates with electronic certificates, this is based on minimizing counterfeiting efforts by land mafias so that the implication is that the number of land disputes in the field will decrease. However, the discourse for modernizing proof of ownership is in line with the increasing development of crime in the electronic (digital) world, therefore the study of the risk of counterfeiting the procurement of electronic certificates is the focus of this research. This research is a normative legal research, which is carried out by examining library materials, which are secondary data and statutory regulations as primary legal materials. This research is a case law approach, legislation, approach, conceptual approach. Based on the research, several legal issues were found, namely, What is the procedural mechanism in procuring electronic certificates according to Agrarian and Spatial Planning Number 1 of 2021? What is the risk of falsification of electronic certificate data according to criminal law?Keywords :Electronin Certificate, Risk, Counterfeiting ABSTRAKDiterbitkannya Peraturan Menteri ATR BPN Nomor 1 Tahun 2021 Tentang Sertifikat Elektronik adalah peraturan bersifat progresif dengan maksud untuk mengganti sertifikat konvensional menjadi sertifikat elektronik, hal ini didasari untuk memperkecil upaya pemalsuan oleh para mafia tanah sehingga implikasinya adalah menurunnya angka sengketa tanah di lapangan. Namun wacana untuk modernisasi bukti kepemilikan ini sejalan dengan meningkatnya perkembangan kejahatan di dunia elektronik (digital), oleh sebab itu kajian resiko pemalsuan terhadap pengadaan sertifikat elekronik menjadi fokus penelitian ini. Penelitian ini adalah penelitian hukum normatif, yang dilakukan dengan cara meneliti bahan pustaka, yang merupakan data sekunder dan aturan perundang-undangan sebagai bahan hukum primer. Penelitian ini Pendekatan Kasus hukum, Perundang-perundangan, Pendekatan, Pendekatan Konseptual. Berdasarkan penelitian tersebut ditemukan beberapa isu hukum yakni, Bagaimana mekanisme prosedural dalam pengadaan sertifikat elektronik menurut Peraturan Agraria dan Tata Ruang Nomor 1 tahun 2021? Bagaimana resiko terjadinya pemalsuan data sertifikat elektronik menurut hukum pidana?Kata kunci : Sertifikat Elektronik, Resiko, Pemalsuan